ChemInform Abstract: Synchronization and Complex Dynamics of Oscillators with Delayed Pulse Coupling. Issue 6 (20th February 2013) - Baer, Markus; Schoell, Eckehard; Torcini, Alessandro
Abstract Review: 29 refs.